Local German Salafists and Saudi Arabia An Unholy Alliance - Jaraba, Mahmoud (Journal of Muslims in Europe, 2023)
Salafism in Germany is often viewed as a product of Saudi Arabia s efforts to spread its conservative brand of Islam around the world. In recent years, the Kingdom has attempted to change its image both domestically and internationally by distinguishing itself from Salafism. The goal of this article is to look at how local Salafists, who have been supported by Saudi Arabia and religiously and ideologically shaped by Saudi Salafi scholars, are attempting to construct a localised and radicalised version of Salafism that is grounded in the German context, while also being critical of Saudi Arabia s social liberalisation.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Christians; Germany; hisba; Jews; Muslim rulers; salafism; Saudi Arabia; wahhabism